Identity / edited by Giselle Walker and Elisabeth Leedham-Green - "Walker,Giselle.(ed.)" (Delhi, 2010)
There is a spectrum of identities: from the mathematical, through cases where specific criteria matter, to the complex or intuitive cases where we can recognise identity but don't know what the criteria should be. In a series of essays by senior figures in the sciences and humanities, this book examines what identity means across a number of academic disciplines. Topics range from mathematics, through the rules of recognition in biology and the law, to comprehending the individual in the visual, performing and literary arts, and ultimately to notions of the philosophy of existence. Using the theme of identity to make new interdisciplinary connections, the contributors offer interested readers a glimpse into their specialist subjects and suggest new ways for students and scholars to think about identity in relation to their own work.
Keywords: Identity(Philosophical aspects)